2020
DOI: 10.1590/s1982-21702020000400018
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Nsdi Ten Years Later: Current Overview, New Challenges and Propositions for National Topographic Mapping

Abstract: Cartographic data represents the main and basic component of a Spatial Data Infrastructure. SDI, in turn, has the role of supporting, with strategic information, the most diverse political and economic actions, in the management and planning of public actions. Thus, this work aims, initially, to present an overview of cartography in Brazil through the analysis of the evolution of topographic mapping coverage in the country. For each of the main scales used, a coverage map was created. The analyzes reflect thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…This is due to the fact that in this case, the reference database is a recent mapping, on the scale of 1:25,000 and updated in the year 2018. When compared with the reality of the country, it is observed that the availability of such an updated and detailed dataset is an exception, according to Silva and Camboim (2020) that calculated that only 5.5% of Brazil's territory is mapped on the 1:25,000 scale, and in this scale, about 68% were less than 12 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the fact that in this case, the reference database is a recent mapping, on the scale of 1:25,000 and updated in the year 2018. When compared with the reality of the country, it is observed that the availability of such an updated and detailed dataset is an exception, according to Silva and Camboim (2020) that calculated that only 5.5% of Brazil's territory is mapped on the 1:25,000 scale, and in this scale, about 68% were less than 12 years old.…”
Section: Resultsmentioning
confidence: 99%
“…However, Brazil has a historical deficiency in the coverage of cartographic data in its territory, noticeable in the larger scales established for the national topographic mapping. According to Silva and Camboim (2020), the 1:25,000 scale, for example, has hugely limited coverage (about 5.5% of the country) incorporated into the National Cartographic System. The intermediate scales, 1:50,000 and 1:100,000, when combined, cover 94% of the country, but on the other hand, mostly produced more than 40 years ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, only 5.5% of the territory has reference mapping on a scale of 1:25,000 (Silva & Camboim, 2020), and on large (urban) scales the numbers are worse. Belo Horizonte (BH), the capital of the State of Minas Gerais, is an exception.…”
Section: Study Casementioning
confidence: 99%
“…In many developing countries, where spatial data deficits are common, both at large and small scales (Silva & Camboim, 2020), voluntary geographic information (VGI) can minimize the consequences of this scenario. In these countries, the focus of research on VGI is updating existing cartographic bases (Bravo & Sluter, 2015; Machado & Camboim, 2019).…”
Section: Introductionmentioning
confidence: 99%